The intergration of international strategies way to sustainable development - Omar, Rusdi; Islam, Rabiul; Khamis, Kamarul Azman (IAEME Publication, 2020)
The aim of this paper was to explore the global managerial strategies way to sustainable development in 4.0 industrial revolutions. The engagement of technology and factory in industrial revolution 4.0 become a crucial part of new ways doing business globally. The issues of pollution prevention, resource conservation, and performance measurement order to manage environmental impact of its operation and environmental practices, application of greenhouse concept, hazardous and nonhazardous waste of disposal, industrial air emissions and wastewater. Data for this study were obtained from existing literatures on industrial revolutions of global managerial studies to sustainable development. The methodology heavily relied on existing previous literatures on the subject being dealt with. The findings indicate that it is a good platform for the government to open up their market and offering a good infrastructure, capacity, technology and supporting policy and encouragement in order to provide a better standard of living, job opportunity, technology exposure, economic circulation and standard. It also discusses the environmental and health issues that alarming, every effort toward sustainable development need to be supported as future generation need place to life, a good climate to enjoyed, green environment to ventures, clear oven to dive-in, good air to breath and most important clean water to drink.